On The Risk of Urban Road Pavement Failure: A Case Study of Owerri, Imo State - Christy C. Nwachi; Harrison O. Amuji; Bridget N. Okechukwu; Kenneth O. Okeke; Samuel I. Ogbaa; John F. Ojutalayo; Louisa N. Amaechi; Emri S. Inaku (International Journal of Urban Design and Development, 2025)
In this research work, we study the risk of road pavement failures in Owerri Imo State. The study deviates from other research work in this area that focused on the nature of road pavement failures without considering the risk involved with respect to human life and others. This was the aspect the study delved into. The researchers used questionnaires to collect primary data from randomly selected respondents on axle load and fatalities within the period under study. The data collected was analyzed using the risk matrix and stochastic processes to determine the long run probability of risk of pavement failures. The risk value was 6.0891, which falls into the rejection region, meaning that a drastic measure is required to reduce the risk imposed on drivers and passengers due to road pavement failures in Owerri. The study also showed that the frequency of pavement failure in Owerri in the long run would lie between the range (26.0, 59.6) with probability 0.2003. Therefore, road pavement failure will account for 20.03% of the total road in Owerri if urgent action is not taken. And for consequence, with probability of 0.2905, the most likely number of fatalities will lie within the range (18.0, 24.0) and will account for 29.05% of the fatality in the long run. These values are reasonably high and unacceptable. Therefore, there is need for drastic risk reduction on road pavement failures in Owerri Imo State. From the study, we made some recommendations to mitigate the imminent risk of road pavement failures in Owerri, Imo State.
Keywords: Markov chain; Road pavement failure; expected risk value; risk matrix; urban planning